The Influence Of Stress Level On The Creep Of Unfilled Rock Joints - Charles W. Schwartz; Subash Kolluru (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
INTRODUCTION Creep of rock in situ, like most rock mass behavior, will be largely governed by the behavior of the natural discontinuities -- bedding planes, faults, and joints, in particular, Several past studies have investigated various aspects of the time-dependent deformation of rock discontinuities; examples include Amadei and Curran (1980), Engelder and Scholz (1976), Johnson (1975), Kaiser and Morgenstern (1979), Solberg et al. (1978), and Wawersik (1974). These studies have provided much insight into the general phenomenon, but they have also produced some inconsistent conclusions and left many unanswered questions. This paper will attempt to shed some light on one of these questions: What is the influence of stress level on the creep of unfilled rock joints? The discussion will follow a two-part approach to the problem: (1) laboratory creep experiments on small scale jointed specimens, (2) a simple theoretical mechanism to explain, at least in qualitative terms, some of the results from the experimental program. EXPERIMENTAL PROGRAM Uniaxial creep tests were conducted on intact and jointed samples of a specially formulated gypsum plaster "synthetic rock." Synthetic rock materials have several advantages over natural rock for long-term creep testing: (a) higher creep rates, (b) lower strength and therefore lower loading requirements, (c) simpler specimen preparation, and (d) more controlled and consistent properties. Gypsum based plasters have been used previously in studies of short-term strength and deformability of jointed samples (Patton, 1966; Einstein and Hirschfeld, 1973). Furthermore, Williams and Elizzi (1977) demonstrated that natural gypsum, at least, creeps in a manner similar to that of most other creep-susceptible natural rocks.